2009
DOI: 10.1242/dev.033795
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog signaling regulates a novel epithelial progenitor domain of the hindbrain choroid plexus

Abstract: Choroid plexuses (ChPs) are vascularized secretory organs involved in the regulation of brain homeostasis, and function as the blood-cerebrospinal fluid(CSF) barrier. Despite their crucial roles, there is limited understanding of the regulatory mechanism driving ChP development. Sonic hedgehog (Shh), a secreted signal crucial for embryonic development and cancer, is strongly expressed in the differentiated hindbrain ChP epithelium (hChPe). However, we identify a distinct epithelial domain in the hChP that does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 33 publications
6
93
1
5
Order By: Relevance
“…Notably, the hindbrain choroid plexus is in close apposition with the cerebellar VZ throughout development (Fig. 4), and it is the only choroid plexus that expresses Shh (13). The observation that the hindbrain medulla, the only other noncerebellar source of Shh within the developing hindbrain system, is not required for expansion of VZ progenitors supports the argument that the hChP contributes to cerebellar VZ development.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Notably, the hindbrain choroid plexus is in close apposition with the cerebellar VZ throughout development (Fig. 4), and it is the only choroid plexus that expresses Shh (13). The observation that the hindbrain medulla, the only other noncerebellar source of Shh within the developing hindbrain system, is not required for expansion of VZ progenitors supports the argument that the hChP contributes to cerebellar VZ development.…”
Section: Discussionmentioning
confidence: 62%
“…Shh signaling activity was not detectable in the cerebellum at E12.5, although evident in the developing hChP at all stages presented ( Fig. 1) (13). Because radial glial cells are localized to the apical surface of the brain ventricular zone and recognized as the major source of neural progenitors in the cerebellum (10), we examined whether Shh signaling is activated in these cells.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…chin chiang (Vanderbilt u. ) demonstrated that Hh signalling also functions earlier in cerebellar development to promote the proliferation of ventricular zone radial glial cells (Huang et al, 2009). However, Shh is not expressed in the cerebellum during these early stages.…”
mentioning
confidence: 99%